Workshop ELLIB (Electronic Library) Sebagai Upaya Peningkatan Pelayanan Pustakawan SMA/SMK/MA Sederajat dan Minat Baca Pemustaka (Jurnal Pengabdian Masyarakat UNAMA, 2023)
This community service activity was carried out in the Adiwangsa University Jambi (UNAJA) meeting room, where the participants were SMA/SMA/MA equivalent librarians in Jambi City. The ELLIB (Electronic Library) Workshop as an Effort to Improve Librarian Services for SMA/SMK/MA Equivalents and Interest in Reading Readers aims to provide motivation and an overview of the transformation of conventional libraries and the Electronic Library (Ellib), to increase the reading interest of librarians (Readers) and high school librarian services /SMK.MA in the Jambi city area, as well as providing training on the application of Ellib (Electronic Library) and compiling a good and correct library resource management system at high school level educational institutions in the Jambi City Region, so that Ellib (Electronic Library) can be implemented in their respective schools -respectively.